2017
DOI: 10.1007/s00223-017-0263-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sequential Treatment with Bisphosphonates After Teriparatide in Ovariectomized Rats: A Direct Comparison Between Risedronate and Alendronate

Abstract: Teriparatide (TPTD), a recombinant human parathyroid hormone N-terminal fragment (1–34), is a widely used bone anabolic drug for osteoporosis. Sequential treatment with antiresorptives such as bisphosphonates after TPTD discontinuation is generally recommended. However, relative effects of bisphosphonates have not been determined. In the present study, we directly compared effects of risedronate (RIS) and alendronate (ALN) on bone mineral density (BMD), bone turnover, structural property and strength in ovarie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…RIS has previously been reported to display a significantly greater potency for fracture prevention in patients with osteoporosis than ALN in the first year of therapy ( Silverman et al, 2007 ). We also reported that RIS might exhibit better effects on the bone quality compared with ALN in rat models ( Yano et al, 2014 ; Yano et al, 2017 ). However, the mechanisms of the distinct effects of each BP remain to be fully understood.…”
Section: Introductionmentioning
confidence: 65%
“…RIS has previously been reported to display a significantly greater potency for fracture prevention in patients with osteoporosis than ALN in the first year of therapy ( Silverman et al, 2007 ). We also reported that RIS might exhibit better effects on the bone quality compared with ALN in rat models ( Yano et al, 2014 ; Yano et al, 2017 ). However, the mechanisms of the distinct effects of each BP remain to be fully understood.…”
Section: Introductionmentioning
confidence: 65%
“…The results of the current study showed an increase in BMD in vertebral trabecular bone with monotherapy of ZA, AL, and RI (27.5% for ZA, 21.3% for RI and 17.7 % for AL). Yano et al (19) reported that RI may have a greater impact on improving bone quality than AL, despite the less prominent effect on BMD. Most studies reported ZA as the most potent drug of bisphosphonates, which significantly increase the BMD and reduce the risk of fractures in comparison to other bisphos-phonates (20).…”
Section: Discussionmentioning
confidence: 99%
“…After micro-CT scan, the right side femur was tested for bone strength by three-point bending test [ 23 ]. The biomechanical testing was done using ElectroPuls E10000 Linear-Torsion all-electric dynamic test instrument (INSTRON, MA, USA).…”
Section: Methodsmentioning
confidence: 99%